Cancer Treatment: Superporous Poly(ethylene glycol) Diacrylate Cryogel with a Defined Elastic Modulus for Prostate Cancer Cell Research (Small 29/2016). Issue 29 (1st August 2016) - Göppert, Bettina; Sollich, Thomas; Abaffy, Paul; Cecilia, Angelica; Heckmann, Jan; Neeb, Antje; Bäcker, Anne; Baumbach, Tilo; Gruhl, Friederike J.; Cato, Andrew C. B.
Abstract : On page 3985, F. J. Gruhl, A. C. B. Cato engineer superporous poly(ethylene glycol) diacrylate cryogels that mimic the stiffness of malignant prostate tissues for studies of prostate cancer cell growth and function. Cells grow in an anchorage‐dependent manner in this scaffold for three weeks and respond to androgen and antiandrogen treatment. Compared to 2D cell culture system, androgen‐dependent prostate target gene expression is highly regulated in this system.